Pengaruh Budaya Organisasi dan Beban Kerja terhadap Kinerja Pegawai di Unit Percetakan Al-Qur'an - Nadzir Ahmad Naliatuski; Muhamad Azis Firdaus; Hannisa Rahmaniar Hasnin (GLOBAL SCIENTS PUBLISHER, 2026)
Employee performance is a key determinant of organizational effectiveness, particularly in public institutions with high production targets and quality standards. This study aims to examine the influence of organizational culture and workload on employee performance at the Al-Qur'an Printing Unit of the Ministry of Religious Affairs of the Republic of Indonesia. A quantitative survey approach was employed involving 98 respondents selected from a population of 130 employees using proportionate stratified random sampling. Data were collected through questionnaires and analyzed using SPSS version 32, including validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination analysis. The findings reveal that organizational culture and workload have positive and significant effects on employee performance, both partially and simultaneously. Organizational culture was identified as the most influential variable. The research model explains 44.5% of the variance in employee performance, while the remaining variance is attributable to other factors beyond the scope of this study.